PEMBANGUNAN MELALUI SEKTOR PERTAMBANGAN DI INDONESIA: SEBUAH TINJAUAN ETIS - Idris, M. Faris (Universitas Yapis Papua, 2013)
AbstractDevelopmentÂ is the most important things in building a nation. Building a nation means giving the people of country, prosperity. From long time ago, the development that applied by many countries was known as Conventional Development. That is the development by using all resources which the state owned, to get more benefit from great exploitation, especially from the natural resources. For country with huge natural resouces like Indonesia, economic fulfillment by mineral eksploration is the fastest way to reach funding for development needs. Year by year eksploration faces Indonesian to an ecological problem nowaday. Several matters then need to be posed: what is actually the development method that enhanced by the government to fulfil the cost of development; why the mining sector was chosen as the way to accelerate the development; who become the winners and which people that lost in this paradigm? By the time, some countries finally face the largest problem from it, the sustainability, that is, it becomes important theme discussed everywhere, because it contains the governmentsâ responsibilities for the future generations